Gestión ambiental de las pymes del sector comercio en el Cantón Machala, Provincia El Oro, Ecuador. - González Ordóñez, Andreína Inés (My University, 2019)
Environmental management includes the set of policies, responsibilities, procedures, processes, actions and environmental practices that are used to improve the environmental performance of companies, thus allowing compliance with environmental regulations and increased competitiveness. The objective of the work is to analyze the elements of environmental management used by pymes in the commerce sector, located in the Machala Canton. For its development the quantitative approach was used, the method used is deductive and the type of research is descriptive with a field design. The technique of data collection was the survey using random sampling. The results show a high percentage of indifference in aspects such as training of workers in environmental issues (25.5%), consideration of environmental aspects in planning (21.6%), measurement of environmental performance (19.6%) , waste reduction (17.6%), introduction of clean technologies (17.6%), knowledge of environmental standards (13.7%), measures to prevent environmental impacts (13.7%) and definition of a policy environmental in the company (13.7%). It concludes on the need to increase environmental management in companies in the commerce sector in order to obtain a better performance of them.
La gestión ambiental comprende el conjunto de políticas, responsabilidades, procedimientos, procesos, acciones y prácticas ambientales que se emplean para mejorar el desempeño ambiental de las empresas, permitiendo así el cumplimiento de la normativa ambiental y el incremento de la competitividad. El objetivo del trabajo fue analizar los elementos de la gestión ambiental que emplean las pymes del sector comercio, ubicadas en el Cantón Machala. Para su desarrollo se empleó el enfoque cuantitativo, el método utilizado fue el deductivo y el tipo de investigación fue descriptiva con un diseño de campo. La técnica de recolección de datos fue la encuesta utilizando para ello un muestreo aleatorio. Los resultados evidencian un elevado porcentaje de indiferencia en aspectos como capacitación de los trabajadores en temas ambientales (25,5%), consideración de los aspectos ambientales en la planificación (21,6%), medición del desempeño ambiental (19,6%), reducción de desechos (17,6%), introducción de tecnologías limpias (17,6%), conocimiento de las normas ambientales (13,7%), medidas para prevenir impactos ambientales (13,7%) y definición de una política ambiental en la empresa (13,7%). Se concluye sobre la necesidad de incrementar la gestión ambiental en las empresas del sector comercio con el fin de obtener un mejor desempeño de las mismas.
Keywords: GESTIÓN AMBIENTAL; PYMES; COMPETITIVIDAD; EMPRESAS